1996
DOI: 10.1063/1.116687
|View full text |Cite
|
Sign up to set email alerts
|

c-axis oriented ferroelectric thin films of PbTiO3 on Si by pulsed laser ablation

Abstract: We have deposited single phase c-axis oriented ferroelectric thin films of PbTiO3 on Si(100) by pulsed laser ablation technique in situ. It has been shown that the formation of a nonferroelectric, Pb2Ti2O6 pyrochlore phase at the interface could be avoided by raising the substrate temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In all the cases, the structure relaxations around V Ti are greater than the others, and the one around V Pb are least. This could account for the experiment result that the crystal structure, lattice parameter were still maintained with the decreasing of Pb/Ti ratio when the V Pb concentration was relatively low[18]. FromTable 1, it could be also found that in the case of V O , the bond length between Ti ion and uppermost O ion becomes shorter (1.8 Å), indicating a stronger hybridization between Ti-O.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In all the cases, the structure relaxations around V Ti are greater than the others, and the one around V Pb are least. This could account for the experiment result that the crystal structure, lattice parameter were still maintained with the decreasing of Pb/Ti ratio when the V Pb concentration was relatively low[18]. FromTable 1, it could be also found that in the case of V O , the bond length between Ti ion and uppermost O ion becomes shorter (1.8 Å), indicating a stronger hybridization between Ti-O.…”
mentioning
confidence: 60%
“…1. V Pb 2− + V O 2+ is also the main defect reported on experiments [18,21]. In the cases of SrTiO 3 and BaTiO 3 , the dominant defect species is V O or V Sr (Ba) 2− + V O 2+ , depending on the thermodynamic condition [11,12].…”
Section: Defect Formation Energymentioning
confidence: 95%
“…1,2 A particularly large volume of research has been devoted to ferroelectrics with the perovskite structure, such as BaTiO 3 , PbTiO 3 , (Pb,La͒TiO 3 , Pb͑Zr,Ti͒O 3 , (Pb,La͒͑Zr,Ti͒O 3 , (Ba,Sr͒TiO 3 , etc. [3][4][5][6][7][8][9] In the last few years, there have also been a few reports on thin films of antiferroelectric materials such as PbZrO 3 , 10-13 which have potential applications in phase switching, charge storage, current sources, and linear capacitors. They can also be used in microelectronic or microelectromechanical devices.…”
Section: Introductionmentioning
confidence: 99%
“…The densely compacted target helped to minimize particulate growth commonly occurring during ablation process and thus improved the film quality. The pulsed laser deposition process used for growing thin films has been described earlier [10]. Deposition conditions such as substrate temperature, substrate to target distance, laser energy and oxygen pressure were optimized so as to achieve single phase, highly insulating thin films (resistivity of the order of 10 8 -10 9 .cm), similar to that of target material.…”
mentioning
confidence: 99%